Mainstreaming biophilic design in residential development in Jakarta: a study with a multi-level perspective - Wurianturi, Indrajati; Siahaan, Tito Summa; Nurzulky, Hamany; Oktavianus, Riza (Institute for Advanced Science Social, and Sustainable Future, 2023)
In the UN's sustainable development program (Sustainable et al. for 2030), it is determined that sustainable cities and communities are one of the goals for achieving in 2030, namely goal no 11. By 2050, the world's urban population will double, making urbanization the most transformative change of the 21st century (UN-Habitat, 2017). It is undeniable that a big city like Jakarta is a city with a high population density. Human life in urban areas increasingly reduces human opportunities to interact with the natural environment, which decreases a person's general well-being (Feandri, 2016). The research will be carried out on reorganizing the city by involving natural elements through a Biophilic Design theoretical approach, a theory that utilizes human nature to be happy to be close to nature (Browning et al., 2014). This theory is claimed to improve its inhabitants' mental and physical health and direct people to take care of the environment on a larger scale.